2019
DOI: 10.1111/bcp.13869
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and translational pharmacology of the cathepsin K inhibitor odanacatib studied for osteoporosis

Abstract: Cathepsin K (CatK) is a cysteine protease abundantly expressed by osteoclasts and localized in the lysosomes and resorption lacunae of these cells. CatK is the principal enzyme responsible for the degradation of bone collagen. Odanacatib is a selective, reversible inhibitor of CatK at subnanomolar potency. The pharmacokinetics of odanacatib have been extensively studied and are similar in young healthy men, postmenopausal women and elderly men, and were qualitatively similar throughout Phase 1 development and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 47 publications
(104 reference statements)
0
26
0
1
Order By: Relevance
“…Nitrile group containing inhibitors have been widely recognized as covalent and reversible inhibitors of a certain class of enzymes that depend on cysteine-mediated nucleophilic attack for catalysis; the nitrile residue traps the sulfur and forms a thioimidate bond ( Figure 15) that hydrolyzes over the time rendering free enzyme. Odanacatib is one of the prime examples of this class of compounds that has been evaluated as a clinical agent, although with limited success [143,144]. Because of nitrile's tunable target engagement nature, this scaffold has been adapted to target other relevant enzymes, including cathepsin.…”
Section: Nitrile-containing Inhibitorsmentioning
confidence: 99%
“…Nitrile group containing inhibitors have been widely recognized as covalent and reversible inhibitors of a certain class of enzymes that depend on cysteine-mediated nucleophilic attack for catalysis; the nitrile residue traps the sulfur and forms a thioimidate bond ( Figure 15) that hydrolyzes over the time rendering free enzyme. Odanacatib is one of the prime examples of this class of compounds that has been evaluated as a clinical agent, although with limited success [143,144]. Because of nitrile's tunable target engagement nature, this scaffold has been adapted to target other relevant enzymes, including cathepsin.…”
Section: Nitrile-containing Inhibitorsmentioning
confidence: 99%
“…In contrast to traditional anti-resorptive therapies, odanacatib, a small-molecule inhibitor of cathepsin K (CTSK), blocks bone resorption without reducing osteoclast numbers. Similar to osteopetrosis patients with impaired osteoclast resorptive activity, clinical trials of odanacatib showed promise to reduce resorption with minimal decreases in bone formation rate [11][12][13][14][15] . However, further development of this therapy was impeded by an off-target increase in cerebrovascular accident incidence in odanacatibtreated patients 16 .…”
mentioning
confidence: 99%
“…5, n. 6, p. 506-519, nov. 2015. Five CPs were studied in this work that present functional structural similarities in which three are mammalian cathepsins: Cathepsin L (hCatL), Cathepsin S (hCatS) and Cathepsin K (hCatK), and two protozoa CPs: cruzain (Cz) from Trypanosoma cruzi and Leishmania mexicana CPB (LmCPB). The human cathepsins are widely studied for being essential targets for cancer and immune system-related diseases (DENNEMÄRKER et al, 2010;STONE et al, 2019). As a result of that, a lot is known of their structures and substrate specificity, having a large number of inhibitors deposited in the ChEMBL data bank (GAULTON et al, 2017).…”
Section: Cysteine Proteasementioning
confidence: 99%
“…The human cathepsins play chief roles in tumor progression, cardiovascular diseases, osteoporosis and arthritis, neurodegenerative diseases and obesity, making them attractive as drug targets (DENNEMÄRKER et al, 2010;OLSON;JOYCE, 2015;STONE et al, 2019).…”
Section: Cathepsin Familymentioning
confidence: 99%
See 1 more Smart Citation